Business Strategy Analysis with SWOT Analysis Approach on Ayam Penyet Hot Jeletot in Bandung Regency - Ramadhan, Dejan Satria; Dinda Aulia Rasyid; Jasmine Cintya Dewi; Nydra Zafira; Muhammad Revo Rajendra Razan; Nuslih Jamiat (Lembaga Riset, Publikasi dan Konsultasi JONHARIONO, 2024)
This study aims to analyze the business strategy of Ayam Penyet Hot Jeletot in Bandung Regency using a SWOT analysis approach. In the economic aspect due to the COVID-19 pandemic, the business has experienced a significant decline in sales, making it important to evaluate the factors affecting business performance. The main focus of this research is to identify internal and external factors that influence the decline in sales, including less strategic location, lack of digital promotion, and limited facilities and resources. This research used quantitative methods with data collection through interviews and questionnaires involving the business owner and customers. The results of the analysis show that the main strengths of the business are its distinctive taste and competitive prices, while weaknesses include the lack of utilization of social media and limited parking capacity. Opportunities can be utilized from the potential of students around the business location, while the main threat is competition with superior competitors.